(untitled) (Journal of Guidance and Counselling Studies, 2022)
Bribery and corruption are cancer worms eating up the fabrics of this nation. Bribery and corruption have affected every sector of the society and has caused a lot of havoc which if nothing is done will bring this nation to a great ruin and downfall. Bribery is a child of corruption which has invaded and spoilt the good values of this nation. This paper therefore focused on reorientation against bribery and corruption and counselling implications. The paper conceptualized bribery, corruption, reorientation and counselling implication. The paper discussed the prevalence of corruption in various sectors of the nation. The paper also highlighted the various forms of corruption which bribery is one of them. It also enumerated some consequences of bribery and corruption on the life of the people and the entire nation. The roles of the counsellor in reorientation of national values were discussed. Counsellors are in the position to control and checkmate this madness called bribery and corruption. Hence the counselling implications were listed to reorient the entire nation against bribery and corruption. The paper therefore recommended that counsellors should offer reorientation of values through their counselling activities.